Assessment of Dental Caries Prevalence Among Bangladeshi School Children (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: Dental caries or tooth decay is one of the most important health problems in human life. In addition, tooth decay is an infectious disease that affects all population Worldwide. The purpose of this study was to determine the Decayed, Missing and Filled Teeth (DMFT) index among a representative sample of 11-16 years old school children in Rangamati district, Bangladesh. Materials and methods: This descriptive and cross-sectional study was performed from 1st October to 30th November, 2016 on 146 children 11- 16 years old students who were conveniently selected from a high school in Kaptai Upazila, Rangamati District to assess the DMFT index. The DMFT index was determined using the standard method suggested by World Health Organization (WHO) and data were analyzed using SPSS software (Version 18.0) and presented as mean ± Standard Deviation (SD). Results: The prevalence of dental caries in permanent dentition was 57.53% and the highest 64.71% in 13 age group in comparison to the other ages (11, 12, 14, 15, and 16) (55.56%, 52.63%, 64.29%, 54.55% and 25.00%) respectively. The mean DMFT for the sample was 1.92 ± 2.36, while the mean DMFT for different age groups (11-16) were 1.67±2.06, 1.68±2.23, 2.45±2.66, 2.29±2.25, 1.09±1.38 and 0.25±0.50 respectively. The prevalence of dental caries was higher in female with DMFT 2.32±2.57 than in males with DMFT 1.60±2.14. Conclusion: According to the results of this study, the mean DMFT scores in 11-16 years old students are lower than the global standards suggested by WHO.JCMCTA 2018 ; 29 (2) : 63-67